Psalm 130 : poetic patterns and social significance - Prinsloo, Gert T. M. (Old Testament Essays, 2002)
Psalm 130 is probably one of the best-known poems in the Hebrew Psalter. The moving plea for forgiveness captured the imagination of generations of believers. The impressive confession of faith gave hope to the hopeless throughout the centuries. Yet very little has been done on the poetic patterning in the poem and its social significance in the concrete circumstances where the poem originated. The purpose of this study is to approach the poem from these two perspectives. The hypothesis is that such an analysis will help the exegete in interpreting the poem against its sociohistorical background.
free